TEORI PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN DAN HADIS - Pranata, Hamdi; Aprison, Wedra (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The main problem in this writing is the Theory of Islamic Education from the Perspective of the Qur'an and Hadith. This is what the construction of Islamic education is important to do considering that the concept of education in the Islamic world is influenced by western world views, many Islamic educational institutions are not based on the Koran and hadith. The purpose of this discussion is the Theory of Islamic Education from the Perspective of the Qur'an and Hadith. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. The results of the research show that in an Islamic view, the essence of educators is Allah SWT, the Prophets and Apostles and the scholars. Therefore, Muslim educators must emulate their characteristics and continue their duties as ideal educators in the Islamic view. significant differences between Islamic and Western (secular) education systems.